Смисложиттєві запити сучасного українця - Опейда, Людмила Миколаївна; Опейда, Людмила Николаевна; Opeida, Liudmyla M. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У межах дослідження розглянуто проблему сенсу людського життя, показано колізії та суперечності в пошуках смисложиттєвих орієнтирів. Останні характеризуються варіативністю відповідей, які не суперечать одна одній, а розкривають доповняльність кожного різновиду рішень. Якщо смисли життя дещо відрізняються, то сенс людського буття полягає в його цілісності, яка в граничних вимірах означується екзистенціалами «з-цілення» й «цілющості», котрі близькі за змістом до понять «екзистенція» та «трансценденція», прийнятих у західній філософії. Відповідність на понятійному рівні вказує на співмірність на рівні запитів-пошуків, а отже, і на схожість очікуваних відповідей. Taking into account the life reality of the modern Ukrainian and the life-meaning inquiries that appear on this basis, the problem of human meaning of life is reviewed in this research. First of all, the actuality of the theme is connected with the social crisis, overlapping on the individual-personal one, which takes the human being in supreme measurements. The last ones are characterized by the variety of answers, which don't contradict each other, but reveal the complement of each solution variation. The purpose of the work is to show the collisions and contradictions in search of life-meaning guides. The results of the work prove that the meaning of life of the modern Ukrainian actually is a task to realize its own personality, a trial for the being to be expressed through the personal actions and the full realization of the own life as a part of world biography of goodness and as a task to make at least one person happy etc. If the meanings of life differ a bit, then the sense of human being lies in its integrity. In supreme measurements of human being integrity is shown as “healing” and “salubrity”. Appointed existentials of integrity are close by its meaning to the concepts “existential” and “transcendence”, accepted in western philosophy. On the conceptual level such conformities point at the proportionality on the search-inquiry level, therefore at the similarity of the expected answers. The conclusions of the work reduce to the recommendations of the deepen learning of the Ukrainian language architectonics, where the usage of the concepts “healing” and “salubrity” is quite organic and legitimate. Moreover, it enlightens the being of the Ukrainian with its usual deep optimism and ideological tolerance. After all through such a local ethno anthropological and ethno national enlightening there takes place an agreement with general anthropological and general existential tendencies.
The Life-meaning Inquiries of the Modern Ukrainian
Keywords: смисл життя; сенс людського буття; цілісність; «з-цілення»; «цілющість»; екзистенція; трансценденція; meaning of life; sense of human being; integrity; “healing”; “salubrity”; existential; transcendence